DIAGNOSIS AND MANAGEMENT OF PERI-OPERATIVE RISK (BLEEDING AND THROMBOSIS) - Uz, Burak (Pergamon-Elsevier Science Ltd, 2014)
[Abstract Not Available]
5th International Eurasian Hematology Congress -- OCT 15-19, 2014 -- Antalya, TURKEY
Keywords: Venous Thromboembolism; Prevention; Events